The impact of the recent migration from Eastern Europe on the UK economy - David G. Blanchflower; Jumana Saleheen; Chris Shadforth (Institute for the Study of Labor (IZA), 2007)
UK population growth over the last thirty-five years has been remarkably low in comparison with other countries; the population grew by just 7% between 1971 and 2004, less than all the other EU15 countries except Germany. The UK population has grown at a faster pace since the turn of the millennium driven primarily by changes in net migration, and in particular from an influx of migrants from eight East European (A8) countries. There appears to be consistent evidence from the Worker Registration Scheme and National Insurance Number applications that approximately 500,000 migrants from the A8 countries had come to work in the UK between May 2004 and late 2006. But other sources suggest approximately half of these workers have likely returned to their country of origin. We argue that, at present, it appears that A8 immigration has tended to increase supply by more than it has increased demand in the UK (in the short run). This migration flow, we argue, has acted to reduce inflationary pressures and to lower the natural rate of unemployment.
urn:nbn:de:101:1-2008042269
Keywords: 330; Einwanderung; Osteuropäer; Internationale Arbeitsmobilität; Makroökonomischer Einfluss; Preisniveaustabilität; Natürliche Arbeitslosigkeit; Großbritannien